Digital Communication Feedback in Customer Complaint Service (Study at Perumda AM Way Rilau Via Whatsapp Messages) - Nabila, Hilla Cahya; Verawati, Noning; Pienrasmi, Hanindyalaila (Indonesian Journal Publisher, 2025)
This study aims to examine the form of digital communication feedback via WhatsApp used in customer complaint services at Perumda AM Way Rilau. The background of this study is based on the importance of maintaining the quality of public services and customer satisfaction, especially in the clean water provider sector. In today's digital era, WhatsApp is one of the most effective media in bridging two-way communication between companies and customers. This study uses a qualitative approach with participatory observation methods, in-depth interviews, and documentation. Informants in the study consisted of complaint service staff and customers who had submitted complaints via WhatsApp. The results of the study show that the forms of feedback used include positive, negative, and neutral feedback. WhatsApp is used as the main media, supported by an internal system called Pass System which helps the process of distributing and resolving complaints more efficiently and quickly. The communication applied reflects responsiveness, clarity of information, and empathy for customers.